2021
DOI: 10.3390/s21082655
|View full text |Cite
|
Sign up to set email alerts
|

Metal-Modified Montmorillonite as Plasmonic Microstructure for Direct Protein Detection

Abstract: Thanks to its negative surface charge and high swelling behavior, montmorillonite (MMT) has been widely used to design hybrid materials for applications in metal ion adsorption, drug delivery, or antibacterial substrates. The changes in photophysical and photochemical properties observed when fluorophores interact with MMT make these hybrid materials attractive for designing novel optical sensors. Sensor technology is making huge strides forward, achieving high sensitivity and selectivity, but the fabrication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 54 publications
(60 reference statements)
0
6
0
Order By: Relevance
“…hemoglobin, albumin) and cells absorption peaks in the UV (200–400 ​nm) and UV–Vis (400–700 ​nm) regions but that do not have fluorescent properties. Hence, the analyte should be isolated for biological samples (by centrifugation or alternative techniques [ 59 ]) to be trustfully quantified by colorimetric assay whereas it is not required when using fluorescent-based approaches [ 31 ]. Moreover, the colorimetric assay used as a benchmark in this study is enzymatic-based.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…hemoglobin, albumin) and cells absorption peaks in the UV (200–400 ​nm) and UV–Vis (400–700 ​nm) regions but that do not have fluorescent properties. Hence, the analyte should be isolated for biological samples (by centrifugation or alternative techniques [ 59 ]) to be trustfully quantified by colorimetric assay whereas it is not required when using fluorescent-based approaches [ 31 ]. Moreover, the colorimetric assay used as a benchmark in this study is enzymatic-based.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the fabrication of colloidal crystal-based sensors is laborious and SPR analysis requires expensive instrumentation. In this view, fluorescent-based detection approaches are preferential since they are easily designed, simple to measure, cost-efficient, and have been therefore widely exploited for the development of detection systems [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…L-Ag/MMT showed more intense absorption than that of bare MMT and L-AgNPs in the 240 to 450 nm range. Additionally, a shift towards higher wavelengths was observed that was probably associated with the plasmonic behavior of the interaction of small AgNPs with MMT particles [35][36][37][38]. XPS characterization was carried out to confirm the loading of L-Ag NPs into the MMT matrix.…”
Section: Characterization Of L-ag/mmt and L-ag/mmt/beeswaxmentioning
confidence: 99%
“…There are several papers that have shown the improvement in SERS enhancement, introducing several techniques such as the combination of metal-organic frameworks (MOFs) with plasmonic metal nanoparticles [34], silver nanoparticles with porous silicon substrate [35], metal-modified montmorillonite [36], AuNRs functionalized zirconiumbased MOFs [37], and etched-spiky Au@Ag plasmonic superstructures [38]. Our system can analyze bacteria samples without labels using a reusable biosensing device made of graphene and AuNRs.…”
Section: Introductionmentioning
confidence: 99%